2.
h(x) = 1/(x - 1)
<em><u>Replace h(x) with y.</u></em>
y = 1/(x - 1)
<u><em>Swap x and y.</em></u>
x = 1/(y - 1)
<em><u>Solve for y.</u></em>
<em><u>Multiply both sides by (y - 1)</u></em>
x(y - 1) = 1
<em><u>Distributive property.</u></em>
xy - x = 1
<em><u>Add x to both sides.</u></em>
xy = 1 + x
<em><u>Divide both sides by x.</u></em>
y = 1/x + 1
<em><u>Replace y with h^-1(x)</u></em>
H^-1(x) = 1/x + 1 is the inverse function for question 2.
4.
h(x) = 4/(x + 2)
<em><u>Replace h(x) with y.</u></em>
y = 4/(x + 2)
<em><u>Swap y and x.</u></em>
x = 4/(y + 2)
<em><u>Solve for y.</u></em>
<em><u>Multiply both sides by y + 2.</u></em>
x(y + 2) = 4
<em><u>Distributive property.</u></em>
xy + 2x = 4
<em><u>Subtract both sides by 2x.</u></em>
xy = 4 - 2x
<em><u>Divide both sides by x.</u></em>
y = 4/x - 2
<em><u>Replace y with h^-1(x)</u></em>
H^-1(x) = 4/x - 2 is the inverse function for question 4.